2022
DOI: 10.1007/s10461-021-03501-8
|View full text |Cite
|
Sign up to set email alerts
|

Migration and Mobility: Correlates of Recent HIV Testing Among Substance Using Female Sex Workers at the Mexico–Guatemala Border

Abstract: The goal of this paper is to determine the association between traveling to engage in sex work in another country and recent access to HIV testing among substance-using female sex workers (FSWs) in the Mexico–Guatemala border region. From 2012 to 2015, through modified time-location sampling and peer referral, 255 FSWs were recruited at Mexico’s southern border. Participants completed questionnaires on sociodemographics, migration and mobility experiences, work environment factors, and substance use. A concept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…Research in China also suggested that HIV infection rates were higher among mobile populations [29], the prevalence of HIV-1 among Burmese injecting drug users (Yunnan-mIDUs) living in Yunnan was 19.0% [30]. Migration and mobility were often connected to vulnerability factors such as substance use, social exclusion and stigma, lack of access to health care or social security services, which could increase the chances of HIV transmission [31]. Potential risk factors for infectious diseases may interact with each other and ultimately increase the risk of disease, and further exploration of the pathways of action of these risk factors is warranted.…”
Section: Introductionmentioning
confidence: 99%
“…Research in China also suggested that HIV infection rates were higher among mobile populations [29], the prevalence of HIV-1 among Burmese injecting drug users (Yunnan-mIDUs) living in Yunnan was 19.0% [30]. Migration and mobility were often connected to vulnerability factors such as substance use, social exclusion and stigma, lack of access to health care or social security services, which could increase the chances of HIV transmission [31]. Potential risk factors for infectious diseases may interact with each other and ultimately increase the risk of disease, and further exploration of the pathways of action of these risk factors is warranted.…”
Section: Introductionmentioning
confidence: 99%